Hop count limitation analysis in wireless multi-hop networks - Liao Wenxing; Wu Muqing; Zhao Min; Li Peizhe; Li Tianze (International Journal of Distributed Sensor Networks)
Recent studies about wireless multi-hop networks mainly focus on two aspects, network performance and network strategy. A mass of models and algorithms about network connectivity, path reliability, and node mobility have been proposed to improve network performance. However, hop count, an important factor of wireless multi-hop networks, is rarely researched. In this article, we propose some feasible research methods to figure out the connections between hop count and network connectivity, and path reliability and node mobility, respectively. By modeling the network connectivity, path reliability, and node mobility, we get the maximum hop count of arbitrary wireless multi-hop network. This study shows that the hop count limitation has great effect on network stability. With an increase in hop count, the network stability gets worse. Thinking about this situation, we propose some feasible advices to avoid the hop count limitation problem, which may provide some useful theoretical foundation for further study on wireless multi-hop networks.